Mathematical Simulation of Cloaking Metamaterial Structures (Advances in Applied Mathematics and Mechanics, 2012)
In this paper we present a rigorousderivation of the material parameters for both the cylinder andrectangle cloaking structures. Numerical results using thesematerial parameters are presented todemonstrate the cloaking effect.